How to report and make sense of a new HIV-1 circulating recombinant form? - Wan, Zhenzhou; Zhang, Chiyu (Frontiers in Microbiology, 2024)
Co-circulation of multiple HIV-1 subtypes in the same high-risk groups leads to the on-going generation of various inter-subtype recombinants, including unique (URFs) and circulating (CRFs) recombinant forms, which brings a new challenge for the prevention and eradication of HIV/AIDS. Identification and prompt reporting of new CRFs will provide not only new insights into the understanding of genetic diversity and evolution of HIV-1, but also an early warning of potential prevalence of these variants. Currently, 140 HIV-1 CRFs have been described; however, their prevalence and clinical importance are less concerned. Apart from the mosaic genomic maps, less other valuable information, including the clinical and demographic data, genomic sequence characteristics, origin and evolutionary dynamics, as well as representative genomic fragments for determining the variants, are available for most of these CRFs. Accompanied with the growing increase of HIV-1 full-length genomic sequences, more and more CRFs will be identified in the near future due to the high recombination potential of HIV-1. Here, we discuss the prevalence and clinical importance of various HIV-1 CRFs and propose how to report and make sense of a new HIV-1 CRF.